If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(t + 7) + -1(t + 5) = 5 Reorder the terms: -2(7 + t) + -1(t + 5) = 5 (7 * -2 + t * -2) + -1(t + 5) = 5 (-14 + -2t) + -1(t + 5) = 5 Reorder the terms: -14 + -2t + -1(5 + t) = 5 -14 + -2t + (5 * -1 + t * -1) = 5 -14 + -2t + (-5 + -1t) = 5 Reorder the terms: -14 + -5 + -2t + -1t = 5 Combine like terms: -14 + -5 = -19 -19 + -2t + -1t = 5 Combine like terms: -2t + -1t = -3t -19 + -3t = 5 Solving -19 + -3t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -3t = 5 + 19 Combine like terms: -19 + 19 = 0 0 + -3t = 5 + 19 -3t = 5 + 19 Combine like terms: 5 + 19 = 24 -3t = 24 Divide each side by '-3'. t = -8 Simplifying t = -8
| 4t+12-10= | | y=20+150 | | 36p-49p^3=0 | | 11m^2+3m=0 | | (X-2)(X+1)-4=0 | | 8x-10y=30 | | 4x-7=-2x+9 | | -3=-31+16.666 | | 0.10(m-100)+15+20=0.05m+40 | | 7t=6 | | 2x-19+3x+6+2x-10=180 | | 17k^2+119k=0 | | 9a-4=14 | | 4x=5y+6 | | A/6=-18 | | -3+9=-21 | | 2a+x=7 | | 3x+(-15+3x)=21 | | 8x-52=x | | 11x-9=8x+6 | | 9g^2+g=0 | | -7/3(y-12)-1/9y | | C-7.2=12 | | 3x^2+36x-8=0 | | 3x^2=19x+14 | | 13=-2+c | | y=ln(x^4+e^2x) | | 4*sin*2x-1=-5 | | -4b^2+81=0 | | 3(20+h)=1 | | f(x)=ln(x^4+e^2x) | | -24=-10a |